Charting the future of CFO’s LINKAPIL Program: a technology platform for innovation through scenario building and relevance tree analysis - Garcia, Rodrigo Visperas Jr.; Imbang, Glen A. (Quezon City University of the Philippines Diliman, 2023)
Thirty-four years ago, the Commission on Filipinos Overseas (CFO) developed an initiative to put a structure to manage donations from Filipinos based overseas and channel these philanthropic deeds toward the country’s local development. Launched by then President Corazon C. Aquino in New York, USA, that same year, it was termed Lingkod sa Kapwa Pilipino (LINKAPIL), which roughly translates to “service to fellow Filipinos.” It was the first-of-its-kind state initiative to engage Filipinos abroad to assist the homeland in promoting development.
Over the course of three decades, it served as a vehicle for Filipinos abroad to course their assistance to support projects in primary education, medical missions, livelihood start-ups, health, and even small-scale infrastructure.
As it looks into the future dominated by artificial intelligence (AI) and other technological advancements, it becomes evident that the Linkapil Program must be sustained and enhanced from the viewpoint of technology management (TM). As can be gleaned from a technology management lens, there is a need to chart and ‘retrofit’ the Program through a technology management outlook. To do that, a technology foresight through Imbang’s ten stages of scenario building (2023) was the tool of choice to plot the Program’s future.
The technology foresight study that was undertaken using Imbang’s 10 Stages of Scenario Building (2023) provided the impetus for coming up with three scenarios that all point to the need to embrace emerging technologies in order for the Linkapil Program to remain sustainable and relevant in the future. It behooves the Program to fully embrace its future infused with digital and technological genes.
Thesis
Keywords: Technology